2017
DOI: 10.1002/ajcp.12172
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Examination of Child Protection Involvement Among Young Adults Accessing Homelessness Services

Abstract: Childhood maltreatment is associated with a variety of young adult adversities including homelessness. This study used linked administrative records to develop a population-level, epidemiological characterization of the child protection histories of young adults accessing homelessness services. The records of all 17- to 24-year-olds receiving homeless services between 2011 and 2014 in San Francisco County, California (n = 2241) were probabilistically linked to statewide child protective service (CPS) records. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The one other study used administrative data to ascertain documented early trauma through records from child protective services in California, USA. 50 Of the included studies, 14 (48%) studies ascertained ACE exposure by use of the CDC-Kaiser Permanente ACE scale, seven (24%) studies used the Childhood Trauma Questionnaire Short Form, and eight (28%) studies used other instruments or scales (appendix p 6). The specific ACE categories that were measured by included studies are reported in table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one other study used administrative data to ascertain documented early trauma through records from child protective services in California, USA. 50 Of the included studies, 14 (48%) studies ascertained ACE exposure by use of the CDC-Kaiser Permanente ACE scale, seven (24%) studies used the Childhood Trauma Questionnaire Short Form, and eight (28%) studies used other instruments or scales (appendix p 6). The specific ACE categories that were measured by included studies are reported in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The one large study that reported a relatively lower prevalence than other studies ascertained ACEs through administrative records. 50 This method of ACE measurement has been shown to underestimate true ACE prevalence given that administrative data capture only reported cases of early trauma. 67 The three smaller studies that reported a relatively higher prevalence than other studies recruited homeless young adults with mean ages ranging from 19•6 years to 22•2 years.…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Triage should include a determination of which of these efforts should be prioritized, in what order they should be prioritized, and feasibility of the adolescent's proactive engagement in choosing service options. Standardization in record-keeping and communication systems would help to address geographic mobility so that adolescents with high geographic mobility can access interventions across systems and sectors (Putnam-Hornstein et al 2017). Funding mechanisms (public assistance and Medicaid, private insurance, parent support payments, food stamps, and other assistance) should be delinked from diagnosis in favor of a guaranteed minimum income approach that is specific to adolescents who lack financial support.…”
Section: Cross-jurisdictional Standardization and Intervention Accessmentioning
confidence: 99%
“…The next three papers leverage unique datasets to understand youth homelessness and inadequate housing in the transition to adulthood. Linked administrative records provide population‐level and prospective data to explore the intersection between child welfare involvement and homelessness (Putnam‐Hornstein, Lery, Hoonhout, & Curry, ; Shah et al., ). Ethnographic data collection embedded within a representative and longitudinal survey of low‐income families illuminates how young Latina mothers navigate housing instability (Elliott, Shuey, Zaika, Mims & Leventhal, ).…”
Section: Summaries Of Contributions In Contextmentioning
confidence: 99%